2012
DOI: 10.7860/jcdr/2012/4535.2614
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Associated Localized Thrombotic Microangiopathy Developing in Early Stage after Renal Transplantation

Abstract: Calcineurin inhibitor induced thrombotic microangiopathy is a rare but well recognized complication of a renal transplantation that occurs in 1% of the patients who are on tacrolimus immunosuppression. Among the other aetiological factors of the "de-novo" Thrombotic Microangiopathy (TMA), the condition especially has to be differentiated from an antibody mediated rejection, as both have different pathogenesis, therapeutic connotations and outcomes.We report a case of a middle aged female renal transplant recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Table 2 as calcineurin inhibitors that could also provoke TMA. 17 In addition, antibody-mediated rejection is within the differential diagnosis and could mimic TMA. 18 Ehrlichiosis is a rare infectious disease that could present with FUO or with 1-13 a wide spectrum of clinical presentations both in transplant recipients and in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 as calcineurin inhibitors that could also provoke TMA. 17 In addition, antibody-mediated rejection is within the differential diagnosis and could mimic TMA. 18 Ehrlichiosis is a rare infectious disease that could present with FUO or with 1-13 a wide spectrum of clinical presentations both in transplant recipients and in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of TMA with fever and graft dysfunction suggests infection, with or without sepsis, or rejection. Clinical picture of TMA induced by human ehrlichiosis can pose significant diagnostic challenge in renal transplant recipients with the background of immunosuppressive medication use such as calcineurin inhibitors that could also provoke TMA 17 . In addition, antibody‐mediated rejection is within the differential diagnosis and could mimic TMA 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A component of medication-related TMA cannot be excluded. TMA caused by calcineurin inhibitors occurs in 1% of patients after transplant and is typically restricted to the kidneys 16. This disease can mimic AMR and a biopsy is required to exclude this.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of tacrolimus-related TMA is not fully understood, however, may be related to a dose-dependent inhibition of prostacyclin, leading to vasoconstriction 17 18. With elevated drug levels, some centres advocate for drug conversion and others alter dosing to aim for normal levels 16. Management is controversial in the presence of normal drug levels.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin inhibitor induced TMA often occurs within weeks following SOT, and the CIs are thought to cause direct endothelial injury and platelet aggregation, although the specific mechanism has not been identified. When this is identified, numerous case studies in multiple different organ systems (lung, liver, kidney solid organ transplant) have reported that changing from one CI to another (tacrolimus to cyclosporine or vice versa) or to another class of medication such as sirolimus or mycophenolate mofetil can prevent further episodes of TMA from occurring [61][62][63][64]. However, the addition of the mTOR inhibitor sirolimus to a calcineurin inhibitor also increases the chance of developing TMA [57,65].…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%